The Ambivalent Identity of Eighteenth-Century London Clubs as a Prelude to Victorian Clublife - Valérie Capdeville (Cahiers Victoriens et Edouardiens, 2015)
From the late seventeenth century to Victorian times, gentlemen’s clubs have always oscillated between norm and dissidence. The ambivalent identity of London clubs can be highlighted through some of their main paradoxes and inherent tensions such as integration/exclusion or publicity/privacy. Some of the first political factions that started to meet in London taverns and coffee-houses during the restoration period fostered a spirit of dissent. However, the eighteenth-century club rapidly developed as both a potential counter power and an efficient tool to reinforce political partisanship. Besides, London clubs were considered as instruments of socialization, as they provided young men with an ideal space for promoting their social integration into a selective network of male affiliation. Belonging to a club implied conforming to social norms of politeness and education. Therefore, club sociability proved the best way to acquire the cultural varnish and the social skills required to become a perfect gentleman. If the strict rules, rituals as well as the socially and sexually exclusive membership of these institutions were supposed to guarantee moderation and social cohesion, excess and provocation could easily lead to the disruption of the moral and social order. Dissident behaviour could embody various degrees of social transgression, ranging from a disregard of social norms to more offending or even criminal attitudes. If some ‘clubmen behaving badly’ were excluded from social or political circles and marginalized, others paradoxically remained prominent social figures. The English club can be considered as a distinctive sociability space. Always hesitating between norm and dissidence, London clubs seem to mirror the specificities of the national character, contributing to model English sociability along new ‘norms’. Furthermore, its persistent elitist and gender-exclusive tradition as well as its evolution in the Victorian period makes it a form of resistance to modernity.